2017
DOI: 10.1186/s12888-017-1204-7
|View full text |Cite
|
Sign up to set email alerts
|

ADHD, comorbid disorders and psychosocial functioning: How representative is a child cohort study? Findings from a national patient registry

Abstract: BackgroundCohort studies often report findings on children with Attention Deficit Hyperactivity Disorder (ADHD) but may be biased by self-selection. The representativeness of cohort studies needs to be investigated to determine whether their findings can be generalised to the general child population. The aim of the present study was to examine the representativeness of child ADHD in the Norwegian Mother and Child Cohort Study (MoBa).MethodsThe study population was children born between January 1, 2000 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 59 publications
2
24
0
6
Order By: Relevance
“…Another possible explanation might be that there is a tendency that children with both ADHD and more pervasive neurodevelopmental disorders are registered under their primary diagnosis only (e.g., autism) in the NPR. The rate of registered comorbidities to ADHD in the NPR is much lower than would be expected [ 35 ]. This could result in a selection bias for the outcome, potentially also related to our exposure of interest, and thus influence the association that we study.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation might be that there is a tendency that children with both ADHD and more pervasive neurodevelopmental disorders are registered under their primary diagnosis only (e.g., autism) in the NPR. The rate of registered comorbidities to ADHD in the NPR is much lower than would be expected [ 35 ]. This could result in a selection bias for the outcome, potentially also related to our exposure of interest, and thus influence the association that we study.…”
Section: Discussionmentioning
confidence: 99%
“…50 One study of ADHD in MoBa, reported a lower proportion of ADHD, less psychosocial adversity, and better child global functioning compared to the general child population, but differences were small, and reasonable generalizability to the general child population was assumed. 51 The oversampling for ADHD symptoms at age 3 years gave about a 5-to 8fold increase in the proportion of ADHD compared with preschool prevalence studies, 34,35 and will have increased the probability of finding true cases given a positive screen result. Our sample included children with psychiatric symptoms other than ADHD, such as oppositional defiant disorder (ODD).…”
Section: Discussionmentioning
confidence: 99%
“…Selection into the cohort has been shown to influence prevalence estimates for several pregnancy‐related exposures and outcomes, but not the association between these exposures and outcomes (Nilsen et al., ). Findings from a recent study suggest that participants in MoBa are representative for the general population with regard to ADHD, even though participants in MoBa have lower prevalence rates of diagnosed ADHD (Oerbeck et al., ). Participants in MoBa also have higher socioeconomic position than the general population (Magnus et al., ; Nilsen et al., ), and a recent Norwegian study found that families with lower socioeconomic position more frequently experience negative life events (Bøe, Serlachius, Sivertsen, Petrie, & Hysing, ).…”
Section: Discussionmentioning
confidence: 99%